The Influence of Work Environment, Job Stress, and Job Satisfaction as Intervening Variables on Turnover Intention of Hotel Employees XYZ - Clara Dini Ayunita; Mulatsih Mulatsih; M. Ali Iqbal; Edi Subarkah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the factors that influence employee turnover intention at Hotel XYZ. The population of this study is all employees at Hotel XYZ with a total sample of 184 employees with an observation period of 2019-2021. The endogenous variables used are job satisfaction and turnover intention, while the exogenous variables used are work environment and work stress. The data analysis method used Structural Equation Model-Partial Least Square (SEM-PLS). The results of the study stated that the work environment and work stress had a positive and significant effect on job satisfaction; the work environment has no effect on turnover intention; work stress has a positive and significant effect on turnover intention; job satisfaction has a significant negative effect on turnover intention; Job satisfaction is able to mediate the relationship between work environment and work stress on turnover intention.